The recovery experience of people who were sex trafficked: the thwarted journey towards goal pursuit - Roderik F. Viergever; Nicki Thorogood; Tamara van Driel; Judith RLM Wolf; Mary Alison Durand (BMC, 2019)
Abstract Background In 2010, a shelter programme was established in the Netherlands to provide social and health services for trafficked people. This article describes how service users in this programme conceptualized and experienced their own process of recovery. Methods In 2012, 14 people of non-Dutch nationality who had been trafficked for the purpose of sexual exploitation were interviewed at all three shelters of the programme. Data analysis followed a grounded theory approach. Results Participants felt a strong need to turn over a new leaf in life, leaving negative experiences of the past behind and moving towards a life with a job, a family and friends. In contrast with their willingness to work towards realizing that future, they experienced a lack of autonomy and a thwarted sense of agency in redressing their present situation. Together with the ostracized nature of their place in Dutch society this left them 'in limbo': a feeling of standing still, while wanting to move forward. This led participants to find it more difficult to deal with problems related to their pasts and futures. They particularly appreciated Dutch language training, vocational skills training and opportunities for volunteer work. Conclusions Participants exhibited a strong desire to fulfil the basic psychological needs of competence, relatedness and autonomy, but were thwarted in pursuing these goals. Seemingly against all odds, while faced with several external regulators that limited their agency to change their situation, participants found ways to pursue these goals, through their enthusiasm for activities that helped them get closer to their envisioned futures (language and skills training and volunteer work). Identifying pathways toward attaining their goals allowed them to hope for a better future. That hope and pursuing their goals helped them to cope with the problems of their past and their worries about the future. Therefore, to facilitate service users' recovery in a post-trafficking setting, there is a need to provide them with opportunities to hope for, pursue and attain their personal goals within the structural boundaries of their situation. A future-orientated, strengths-based approach towards service provision and responsive and supportive environments help to do this.